Lessons learned from a collaborative multidisciplinary design studio exploring urban building-integrated agriculture - Gwynne Á Mhuireach; Anna Carolyn Perry; Meghna Jain; Gail Langellotto (Urban Food Systems Symposium, 2024)
Urban agriculture is becoming increasingly critical to promote nutritional security, community resilience, and equitable access to healthy foods for city-dwellers. However, the lack of open space and high cost of land limit the establishment of new urban farms and gardens. One innovative solution is to produce food on and in buildings through rooftop farming, green facades, and controlled environment agriculture. Sustainability co-benefits can be gained by creating a closed-loop system where building outputs are recycled as inputs to the agricultural system, and agricultural outputs ultimately provide inputs to building systems and users. Despite the promise of such building-integrated agriculture (BIA), examples of commercial BIA food production are scarce, due, in part, to the lack of an established framework to provide horticultural expertise during planning, design, and construction of buildings that have substantial crop production components. While the USDA and others have published several toolkits and guides for urban agriculture, which provide very basic resources and advice aimed primarily towards ground-based production, actionable information for architects and building owners looking to include a significant BIA component in new and retrofit construction projects is nearly nil. We posit that successful BIA design teams will likely need to have a horticultural or agricultural consultant during the design process. To explore the ramifications of this novel collaboration between two disciplines that rarely interact, University of Oregon offered an architectural design studio that engaged students enrolled in an Oregon State University special topics seminar as horticultural “consultants” during Spring Term, 2024. The site for the studio’s hypothetical project was Zidell Yards, the last remaining large parcel fronting the Willamette River in Portland, Oregon. It has a long history as an industrial ship-breaking facility and, thus, suffers from soil contamination, making it unsuitable for traditional ground-based urban agriculture. We brought in Extension professionals, practicing architects, horticultural experts, and marketing/production specialists to provide guest lectures and critiques of students’ work. By the end of the term student teams had generated innovative BIA designs that offered key social goods and ecosystem services. Several lessons were learned about the collaborative process between these disparate disciplines, including the usefulness of access to digital visual collaboration tools, the importance of prioritizing communication and trust-building, and the need to begin with shared understandings of team members’ roles and effort commitments.
Keywords: Food security; resilience; architecture; ecological engineering; horticulture; interdisciplinary; pedagogy